Balancing Search and Stability: Interdependencies Among Elements of Organizational Design - Rivkin, Jan W.; Siggelkow, Nicolaj (Management Science, 2003)
We examine how and why elements of organizational design depend on one another. An agent-based simulation allows us to model three design elements and two contextual variables that have rarely been analyzed jointly: a vertical hierarchy that reviews proposals from subordinates, an incentive system that rewards subordinates for departmental or firm-wide performance, the decomposition of an organization's many decisions into departments, the underlying pattern of interactions among decisions, and limits on the ability of managers to process information. Interdependencies arise among these features because of a basic, general tension. To be successful, an organization must broadly search for good sets of decisions, but it must also stabilize around good decisions once discovered. An effective organization balances search and stability. We identify sets of design elements that encourage broad search and others that promote stability. The adoption of elements that encourage broad search typically raises the marginal benefit of other elements that provide offsetting stability. Hence, the need to balance search and stability generates interdependencies among the design elements. We pay special attention to interdependencies that involve the vertical hierarchy. Our findings confirm many aspects of conventional wisdom about vertical hierarchies, but challenge or put boundary conditions on others. We place limits, for instance, on the received wisdom that firm-wide incentives and capable subordinates make top-level oversight less valuable. We also identify circumstances in which vertical hierarchies can lead to inferior long-term performance.